Rotor end factors for 2-D FEA of induction motors with smooth or slitted solid rotor - Shanming Wang; Ziguo Huang; Yuguang Sun; Haixiang Cao (CES Transactions on Electrical Machines and Systems, 2017)
Modifying the equivalent rotor resistivity with rotor end factor in 2-dimension (2-D) finite element analysis (FEA) is an effective way to analyze the 3-dimension (3-D) solid rotor problems. For the smooth solid rotor, five different rotor end factors are discussed and compared with each other. It is theoretically clarified that the resistivity of rotor in 2-D FEA should be multiplied by the square of rotor end factors to take the 3-D end effect of solid rotor into account. For the slitted solid rotor, an improved rotor end factor is proposed based on the equivalent area algorithm of eddy currents in rotor, since the end factors of smooth solid rotor are not applicable. Finally, the time-harmonic finite element method (FEM) combined with the rotor end factor is applied to analyze the performance of solid rotor induction motor. The tested and computed results are in good agreement, which proves the effectiveness of rotor end factor for the simplication of 3-D solid rotor problems.